KOMPETENSI GURU DI MTS AL-IJTIHADIYAH MARTEBING - Putri Fajariah; Salwa Riswanda Sinaga; Ade Irma; Memen Permata Azmi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This journal discusses in depth the competence of teachers at MTs Al-Ijtihadiyah Martebing, with a special focus on how teachers understand and convey lesson material effectively, choose appropriate learning methods, and manage the class well. This research was conducted using interview and observation methods, which aimed to analyze the teaching practices implemented by teachers, as well as the efforts they made to improve their professional competence. The research results show that good communication skills, the use of interactive learning methods, and the implementation of appropriate evaluations are very important in creating a conducive and supportive learning environment for students. With the right approach, teachers can not only improve students' understanding, but also encourage their active participation in the learning process.